Acclimatization of plants produced by in vitro culture - da Silva, Antonio Tadeu; Pasqual, Moacir; Ishida, Jorge Susumu; Antunes, Luís Eduardo Corrêa (Pesquisa Agropecuaria Brasileira, 1995)
The purpose of the present work was to study the effects of age of in-vitro rooting, substrate, and species, on the acclimatization of plants grow from explants under tissue culture conditions in green-house. The species used were Kielmeyera coreacea, Manihot esculenta, Ipomoea batatas and Rubus idaeus, at three ages: 0-3, 7-10 and 15-18 days after rooting, and four substrates: a) soil (purple latosol - of high argillaceous texture) + sand + (1:1:2); b) organic compost; c) commercial organic compost and d) vermiculite. The best surviving index is related to species, and it is not affected by substrate or by age of rooting, but seven days after in-vitro rooting the plantlets showed better tolerance to acclimatization, which is a characteristic of each species. The leaf number showed linear response to all species until 35 days after the beginning of the experiment. Manihot esculenta showed the best leaf area growth, in spite of exhibiting difficulties for acclimatization.